2020
DOI: 10.1186/s12916-020-01545-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of introducing national seasonal influenza vaccination for adults aged 60 years and above in mainland China: a modelling analysis

Abstract: Background: China has an aging population with an increasing number of adults aged ≥ 60 years. Influenza causes a heavy disease burden in older adults, but can be alleviated by vaccination. We assessed the cost-effectiveness of a potential government-funded seasonal influenza vaccination program in older adults in China. Methods: We characterized the health and economic impact of a fully funded influenza vaccination program for older adults using China-specific influenza disease burden, and related cost data, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 30 publications
0
45
1
Order By: Relevance
“…Only a few developed cities such as Beijing have provided free influenza vaccination for older adults using local revenue and have achieved a remarkable increase in local vaccine uptake 56 . In addition, a recent cost-effectiveness study suggests that government fully funded immunization against influenza among older adults proves to be cost-effective for influenza control and prevention in China 57 . Our findings collectively with this evidence inform immunization recommendations in China.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few developed cities such as Beijing have provided free influenza vaccination for older adults using local revenue and have achieved a remarkable increase in local vaccine uptake 56 . In addition, a recent cost-effectiveness study suggests that government fully funded immunization against influenza among older adults proves to be cost-effective for influenza control and prevention in China 57 . Our findings collectively with this evidence inform immunization recommendations in China.…”
Section: Discussionmentioning
confidence: 99%
“…Over 65 years: In 23 of 25 studies, vaccination was considered cost-effective [ 121 122 123 124 125 126 127 128 129 130 131 132 133 134 135 136 137 138 139 140 141 142 143 144 145 ]. The studies were carried out with economic models in 20 countries (including eight countries in the Americas) and analyzed vaccination with trivalent vaccine, or CE of the use of high-dose trivalent, with adjuvants, or quadrivalent.…”
Section: Resultsmentioning
confidence: 99%
“…In Japan, it was found that increasing the subsidy amount by 1000 yen (USD10) led to a one percentage point increase in the vaccination rate among the elderly, thus improving their health outcomes [ 26 ]. In China, a cost-effectiveness study estimated that the threshold vaccination cost is 71.48 yuan (USD10.19) to achieve a fully funded vaccination program for older adults aged ≥60 years [ 27 ]. In the future, combining the financing sources for influenza vaccination (individuals, health insurance, and government) may become a promotive policy signal for individuals to vaccinate against influenza.…”
Section: Discussionmentioning
confidence: 99%